Top of the feud chain - Harrison, Lisi (Harrison, Lisi. Alphas., 2011)
Three women try to deal with matters of the heart and their desire for worldwide fame and success as they compete at the exclusive Alpha Academy, where billionaire Shira Brazille nurtures dancers, writers, musicians, and inventors and sends home anyone she thinks does not measure up to her standards.